Earthquakes - Branley, Franklyn M. ([s.l.] : HarperCollins Publishers, 1990)
Discusses why earthquakes happen, what their sometimes devastating effetcs can be, where the danger zones are, and what measures people can take to safeguard themselves
Keywords: Earthquakes -- Juvenile literature